Effect of the Flow Curve Determination on the Thinning of Drawn Parts - Kölüs, Martin László; Borbély, Richárd; Szőke, Dániel Gyula; Béres, Gábor József (International Journal of Engineering and Management Sciences, 2023)
This study presents the results of finite element simulations based on different variations of the flow curve of DC04 automotive thin sheet. The aim of our research is to investigate how different flow curve equations affect the variation of sheet thickness in cup drawing tests. In order to exclude other influencing factors in the experiment, both the sheet material and the geometric properties of the specimen, as well as the external state factors were considered to be the same in all cases. The finite element simulations were performed using Simufact 2021.1 software. Our results shows that there are no significant differences in wall thicknesses until we reach the zone of double necking, where essential differences are observed.